2004
DOI: 10.1098/rspb.2003.2558
|View full text |Cite
|
Sign up to set email alerts
|

The gall of subordination: changes in gall bladder function associated with social stress

Abstract: Diverse physiological and behavioural mechanisms allow animals to effectively deal with stressors, but chronic activation of the stress axis can have severe consequences. We explored the effects of chronic social stress on agonistic behaviour and gall bladder function, a critical but widely neglected component of stress-induced gastrointestinal dysfunction. Prolonged cohabitation with dominant individuals elicited behavioural modifications and dramatically increased bile retention in subordinate convict cichli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Pathological reactions such as bile retention and immunosuppression were also reported for cichlid s-males (Faisal et al 1989, Earley et al 2004. Permanent stress affects testis development negatively (Wendelaar Bonga 1997, Celino et al 2009, Schreck 2010, Trubiroha et al 2011) and this conclusion is also supported by the observation that temperature decrease leads to spermatogenic arrest at late pachytene spermatocytes in sexually mature Nile tilapia males (Vilela et al 2003).…”
Section: Social Hierarchy and Spermatogenesis In D-and S-malessupporting
confidence: 73%
“…Pathological reactions such as bile retention and immunosuppression were also reported for cichlid s-males (Faisal et al 1989, Earley et al 2004. Permanent stress affects testis development negatively (Wendelaar Bonga 1997, Celino et al 2009, Schreck 2010, Trubiroha et al 2011) and this conclusion is also supported by the observation that temperature decrease leads to spermatogenic arrest at late pachytene spermatocytes in sexually mature Nile tilapia males (Vilela et al 2003).…”
Section: Social Hierarchy and Spermatogenesis In D-and S-malessupporting
confidence: 73%
“…Subordinate animals have been reported to decrease movement rates, modify their spatial orientation, lose body mass, increase their level of risk assessment, and experience suppression of humoral immunity (e.g. Earley, Blumer & Grober, 2004). Increased testosterone and corticosteroid levels, often associated with winning and losing experiences, respectively, can decrease immune system responses (Buchanan, 2000 ;Casto, Nolan & Ketterson, 2001) but it is unknown whether these hormones exert independent influences on immune suppression (Slater & Schreck, 1993;Casto et al, 2001).…”
Section: Mechanisms Of Experience Effectsmentioning
confidence: 99%
“…Amatitlania nigrofasciata has also been frequently used in fish behaviour studies (Arnott et al, 2011;Dechaume-Moncharmont et al, 2011;Moscicki et al, 2011;Chee et al, 2012;van Breukelen, 2013). In one behaviour study, social stress was reported to be associated with gallbladder hypertrophy and increased bile retention (Earley et al, 2004). This study aims to determine and document the detailed macroscopical and histological structure of the AT of A. nigrofasciata.…”
Section: Introductionmentioning
confidence: 99%